Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen Holland Bakery Dengan Keputusan Pembelian Sebagai Variabel Intervening Pada Masyarakat Sunter Jakarta Utara - Risqy Aziz Basuki; Sendi Nurafni (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to determine and explain the effect of Service Quality on Purchase Decisions, the influence of Service Quality on Consumer Satisfaction, the influence of Purchase Decisions on Consumer Satisfaction, the influence of Purchase Decisions in mediating Service Quality on Consumer Satisfaction. The method used in this study is a quantitative method. The results showed that Service Quality had a positive and significant effect on Purchase Decisions, Purchase Decisions had a positive and significant effect on Consumer Satisfaction, Service Quality had a positive and significant effect on Consumer Satisfaction, and Purchasing Decisions could be a mediating variable of Service Quality on Consumer Satisfaction.Keywords: Consumer Satisfaction, Purchase Decisions, Service Quality